2021
DOI: 10.1021/acs.chemrev.1c00447
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Methane to C2Hydrocarbons in Solid-State Membrane Reactors at High Temperatures

Abstract: Direct conversion of methane to C2 compounds by oxidative and nonoxidative coupling reactions has been intensively studied in the past four decades; however, because these reactions have intrinsic severe thermodynamic constraints, they have not become viable industrially. Recently, with the increasing availability of inexpensive “green electrons” coming from renewable sources, electrochemical technologies are gaining momentum for reactions that have been challenging for more conventional catalysis. Using solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 335 publications
0
16
0
Order By: Relevance
“…Figure 2 represents natural gas's direct and indirect conversion into higher-value chemicals. Syngas has become the industrially favored method for the indirect conversion of natural gas into higher-value chemicals and fuels because it is more efficient than the direct conversion methods that are currently available [24].…”
Section: Synthesis Gas Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 represents natural gas's direct and indirect conversion into higher-value chemicals. Syngas has become the industrially favored method for the indirect conversion of natural gas into higher-value chemicals and fuels because it is more efficient than the direct conversion methods that are currently available [24].…”
Section: Synthesis Gas Productionmentioning
confidence: 99%
“…The reaction mixture will be close to equilibrium at high methane conversion [28]. This process uses pure oxygen that is produced using low-temperature separation vessels; therefore, it has a high cost because pure oxygen production comprises about 40% of the total syngas plant cost [24]. Other methods for producing pure oxygen at lower costs, such as using membrane technology, are still in the research stage [26,28].…”
Section: Steam Reformingmentioning
confidence: 99%
“…Switching to methane‐based ethylene production could lower operating temperatures and enhance energy efficiency. This transformation is considered a grand challenge in catalysis and could occur via conventional thermochemical, [87] chemical looping, [88] membrane, [89] electrochemical, [90] or plasma‐based approaches [91] . An emerging and much more effective ethylene decarbonization pathway is emerging via CO 2 hydrogenation reaction and via the eCO 2 RR approach described above.…”
Section: Perspectives On Randd Needsmentioning
confidence: 99%
“…13,14 Earlier studies were carried out to maximize C 2 yield by varying the composition of catalyst and reaction parameters, but economic evaluation revealed that the selectivity of C 2 hydrocarbons is more important than C 2 yields. 8,15 Studies say that catalysts play the primary role in producing C 2 hydrocarbons that affect methane conversion and C 2 selectivity in OCM. To date, several catalysts have been developed; including lanthanide series oxides [16][17][18] , Na-W-Mn mixed metal oxides 19 , and alkaline-earth metal oxides [20][21][22] for OCM reaction.…”
Section: Introductionmentioning
confidence: 99%